2002
DOI: 10.1001/archinte.162.12.1368
|View full text |Cite
|
Sign up to set email alerts
|

The Increasing Incidence of Coronary Artery Disease and Cardiovascular Risk Factors Among a Southwest Native American Tribe

Abstract: Background: Rates of cardiovascular disease and its risk factors seem to be increasing in American Indian populations, yet these changes have received little documentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 13 publications
1
15
0
1
Order By: Relevance
“…Consistent with the other study [2] that suggests that coronary artery disease increases with increasing population age, we observed an incremental trend in prevalence of risk factors with the progress of age.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Consistent with the other study [2] that suggests that coronary artery disease increases with increasing population age, we observed an incremental trend in prevalence of risk factors with the progress of age.…”
Section: Discussionsupporting
confidence: 92%
“…Pattern of CAD risk factors has shown vast disparities between different populations. It has been suggested that the rate of CAD will progressively develop with increasing population age [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] For example, in Ontario, hospital admissions because of ischemic heart disease doubled in Aboriginal communities between 1981 and 1997, whereas over the same period the rates in the general population declined. 1 A major contributing factor appears to be the development of an excessive burden of cardiovascular risk factors in North American Aboriginal populations, most notably dramatic increases in the prevalence of diabetes mellitus.…”
mentioning
confidence: 99%
“…However, following the recognition of an epidemic of ischaemic cardiovascular disease within the American Indian population [8,[29][30][31][32], the first American Indian cardiovascular program (Center of Excellence) within the Indian Health Service (IHS) was initiated in 1993, based out of the University of Arizona as an academic-IHS collaborative focussed on the provision of culturally respectful cardiovascular prevention and treatment of this population and was known as the Native American Cardiology Program (NACP) [33]. The NACP in collaboration with many federal agencies as well as state and non-profit organisations, developed clinically aggressive guideline-driven prevention, detection and early intervention activities directed towards CVD in this population.…”
Section: United Statesmentioning
confidence: 99%